REVIEW OF SHARIA ECONOMIC LAW ON THE POSITION OF COINS OBTAINED IN THE SNACK VIDEO APPLICATION (STUDY OF STUDENTS IN PONTIANAK CITY) - tanassy, rika putri (Universitas Muhammadiyah Pontianak, 2024)
With a mission feature that earns coins that can be converted into money, the video snack program offers a variety of information through films. The application has a wide range of missions, such as watching videos, inviting friends, and liking and following other users. The Snack Video application was developed as a platform for offering different items, and it offers advantages to its consumers. The majority of the material in the snack video application may be utilized as a platform to sell different kinds of items in addition to being used for enjoyment. The Snack Video app is being widely used by companies as an efficient short video platform for product promotion. Coins are awarded to users who complete missions, but some users feel that this is unfair to them and that they should not receive their rights. This makes it necessary to investigate the user's rights to coins that he was not able to obtain. The purpose of this study is to investigate how the position of coins retrieved from the video snack application relates to the review of sharia economic law. This study employs a qualitative methodology combined with a qualitative descriptive method. Two religious leaders and twenty informants (students) in Pontianak City were interviewed as part of the data-gathering methodology, with information gathered through documentation and interviews. The findings indicated that eight informants were unfamiliar with the word